2020
DOI: 10.1177/0972150920931060
|View full text |Cite
|
Sign up to set email alerts
|

Are Time Management and Cyberloafing Related? Investigating Employees’ Attitudes

Abstract: Time is a critical commodity both for individuals and companies because it is not possible to substitute or purchase it. The concept of time management, therefore, attracted the attention of both academicians and practitioners. Companies started to question behaviour of employees using their companies’ Internet access for non-work-related purposes during work hours. These activities constitute an unproductive use of time and detract employees from completing their work demands. In this framework, the purpose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Recently, scholars have turned to examining the impact of time management on cyberloafing. Ötken et al (2020) found a negative relationship between the extent of time wasted and serious cyberloafing but a positive relationship between time planning/attitude and minor cyberloafing. They argued that inefficient use of time prevents time wasters from engaging in serious cyberloafing, while individuals with good time management and positive time attitude are able to complete their tasks ahead of time, consequently allowing them to engage in minor cyberloafing as a respite.…”
Section: Review Resultsmentioning
confidence: 99%
“…Recently, scholars have turned to examining the impact of time management on cyberloafing. Ötken et al (2020) found a negative relationship between the extent of time wasted and serious cyberloafing but a positive relationship between time planning/attitude and minor cyberloafing. They argued that inefficient use of time prevents time wasters from engaging in serious cyberloafing, while individuals with good time management and positive time attitude are able to complete their tasks ahead of time, consequently allowing them to engage in minor cyberloafing as a respite.…”
Section: Review Resultsmentioning
confidence: 99%
“…Scholars also posit that employees' tendency to engage in cyberloafing can be influenced, positively or negatively, by other psychological variables (Zoghbi-Manrique- , such as state of mind or workplace anomia (Zoghbi-Manrique-De-Lara, 2007), technostress (G€ u gerçin, 2020), ability to hide (Askew et al, 2014) or deceive (Lowe-Calverley and Grieve, 2017), entertainment (Chen et al, 2011), a high need for achievement (Cheng et al, 2020) [5], lack of self-control (Restubog et al, 2011), future orientation (Zhang et al, 2015) and emotional exhaustion (Koay, 2018). In a recent study, € Otken et al (2020) determined that employees' attitudes toward time management had a differential impact on the type of cyberloafing wherein the dimension of time wasters negatively explained variance in serious activities, while time planning and attitude positively explained the same for minor activities of cyberloafing.…”
Section: Antecedents and Stakeholdersmentioning
confidence: 99%
“…Scholars generally conceptualized CL as a form of workplace production deviance (e.g., Lim, 2002;Lim & Teo, 2005). Engaging in cyberloafing during working hours is time-consuming and distracts employees from completing their work demands (Otken, Bayram, Besser, & Kaya, 2020). Earlier studies consistently suggested that CL is prevalent and is a perennial cause of concern for many companies (Block, 2001;Lim, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…CL might also expose companies to legal liability in the form of harassment (e.g., employees emailing sexist or racist jokes to co-workers or people outside the organization). Cyberloafing appears to be a recent topic with scanty literature on cyberloafing (Otken et al, 2020). The literature on CL has been limited to its effect on work productivity (Lim & Chen, 2012); employee's work attitude (Lim & Teo, 2009); employee's job satisfaction and commitment (Hartke, 2008), and attitude toward time management (Otken et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation